Relevance of An Expert Witness Report Submitted as Evidence in a Case - Z. V. Trifonova (Теория и практика судебной экспертизы, 2017)
The expert witness report plays a crucial part in any type of forensic investigation; forensic engineering and land surveying are no exception. This article focuses on relevance as a major criterion in the evaluation of a forensic expert’s report. The author identifies the main factors that shape the characteristics of this type of evidence that ensure the relevance of expert opinion in criminal, civil, or administrative proceedings